OPTIMIZATION OF EMPLOYEE ATTENDANCE SYSTEM IN EFFORTS TO IMPROVE OPERATIONAL EFFICIENCY OF TIRTA NENE MALLOMO REGIONAL WATER COMPANY (PDAM) - Izharul Haq Lamada; Asrini Asrini; Nasri Nurul Ramadhan (Universitas Ichsan Sidenreng Rappang, 2024)
The Regional Water Utility (PDAM) Tirta Nene Mallomo is a vital entity in providing drinking water services to the community. Operational efficiency is crucial to ensure smooth service delivery. Managing the employee attendance system is an important aspect of achieving this efficiency. This community service initiative aims to guide students in the Community Service Program (KKN) and propose solutions to help optimize the employee attendance system to enhance operational efficiency. The activities involve the stages of student orientation, implementation, and evaluation, with the significant role of field supervising lecturers. In addition to offering practical solutions, participants are provided with guidelines on simplifying attendance management through an innovative approach focused on the operational needs of PDAM Tirta Nene Mallomo. The proposed solutions include the implementation of an automated attendance system utilizing the latest technology and the establishment of clear policies and procedures. By optimizing the employee attendance system, PDAM Tirta Nene Mallomo can streamline its operations, improve resource allocation, and ultimately enhance the services provided to the community. This initiative not only delivers practical benefits but also offers valuable experiences for KKN students in contributing to the improvement of community welfare.